Стратегії і тактики переговорів в консалтингу - Серських, Надія Сергіївна; Серских, Надежда Сергеевна; Serskykh, Nadiia (My University, 2018)
UK: Проаналізовано теоретичні підходи до стратегій і тактик ведення переговорів у консалтингу, розглянуто основні можливі стратегії, тактики та технології ведення переговорів, проаналізовано основи створення довгострокових відносин між експертами-консультантами та споживачами консалтингових послуг. Визначено принципи ведення переговорів в консалтингу. EN: The theoretical approaches to the strategies and tactics of consulting negotiations are analyzed, the main possible strategies, tactics and technology of negotiations are considered, the foundations of the establishment of long-term relations between consultant experts and consumers of consulting services are analyzed. The principles of conducting negotiations in consulting are determined.
Strategies and tactics of negotiation in consulting
Keywords: переговори; переговори в консалтингу; консалтинг; стратегії переговорів; тактики переговорів; принципи переговорів; консалтингова послуга; negotiations; negotiations in consulting; consulting; negotiation strategies; negotiation tactics; negotiation principles; consulting servise